In vivo redox metabolic imaging of mitochondria assesses disease progression in non-alcoholic steatohepatitis. Issue 1 (December 2017) - Nakata, Ryosuke; Hyodo, Fuminori; Murata, Masaharu; Eto, Hinako; Nakaji, Tomoko; Kawano, Takahito; Narahara, Sayoko; Yasukawa, Keiji; Akahoshi, Tomohiko; Tomikawa, Morimasa; Hashizume, Makoto
Abstract Given the rising incidence of non-alcoholic fatty liver disease (NAFLD) in both adults and children, the development of a non-invasive diagnostic method for assessing disease progression to non-alcoholic steatohepatitis (NASH) has become an important research goal. Currently available non-invasive imaging technologies are only able to assess fat accumulation in the liver. Therefore, these methods are not suitable for a precise diagnosis of NASH. The standard diagnostic technique for NASH, liver biopsy, has several drawbacks, including the higher risk of complications that accompanies invasive procedures. Here, we demonstrated thatin vivo mitochondrial redox metabolism was dramatically altered at an early stage, before histopathological changes, and NASH could be accurately diagnosed byin vivo dynamic nuclear polarization-magnetic resonance imaging, with carbamoyl-PROXYL as a molecular imaging probe. In addition, this technique was feasible for the diagnosis of NASH compared with histopathological findings from biopsies. Our data reveal a novel method for monitoring the dynamics of redox metabolic changes in NAFLD/NASH.